Between State and Society: Government Communication Strategies and Stakeholder Collaboration for Tourism Development in the Pantai Batee Puteh Area, West Aceh - Fadhil, Muhammad; Zulkarnain, Zulkarnain; Zulkarnaini, Zulkarnaini; Juliansyah, Rollis (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the local government’s communication strategies in the development of the Batee Puteh Beach Tourism Area in Aceh Barat Regency. The research focuses on how communication is utilized to address weak promotion and limited stakeholder collaboration. Employing a descriptive qualitative approach, data were collected through field observations and in-depth interviews with relevant officials and local community leaders. The findings reveal that the local government’s communication strategies include: (1) community socialization and engagement through a participatory approach; (2) destination promotion using social media, mass media, events, and cross-sector partnerships; and (3) stakeholder coordination involving government, private sector, community, academia, and media. These strategies have effectively increased community participation and tourist visits. Persuasive communication rooted in local wisdom and informal interactions has also been employed to align stakeholder visions. The study demonstrates that well-designed and executed communication can bridge gaps in information and coordination, positioning communication as a key factor in local tourism development. The novelty of this study lies in identifying a collaborative, participatory government communication model tailored to community-based tourism. It recommends continued communication innovation, stronger destination branding, crisis communication protocols, and long-term cross-sector partnerships. The theoretical implications contribute to social sciences, particularly in development communication and sustainable tourism governance.